2022
DOI: 10.1038/s41418-022-00998-x
|View full text |Cite
|
Sign up to set email alerts
|

Non-coding RNAs and ferroptosis: potential implications for cancer therapy

Abstract: Ferroptosis is a recently defined form of regulated cell death, which is biochemically and morphologically distinct from traditional forms of programmed cell death such as apoptosis or necrosis. It is driven by iron, reactive oxygen species, and phospholipids that are oxidatively damaged, ultimately resulting in mitochondrial damage and breakdown of membrane integrity. Numerous cellular signaling pathways and molecules are involved in the regulation of ferroptosis, including enzymes that control the cellular r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(40 citation statements)
references
References 180 publications
0
33
0
Order By: Relevance
“…Although many studies have discovered the detailed mechanism and critical signaling pathways of ferroptosis, the mechanism of ncRNAs, especially circRNAs, in the occurrence and progression of ferroptosis is still unclear [ 19 ]. Only a few studies have revealed the role of circRNAs in ferroptosis and GBM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many studies have discovered the detailed mechanism and critical signaling pathways of ferroptosis, the mechanism of ncRNAs, especially circRNAs, in the occurrence and progression of ferroptosis is still unclear [ 19 ]. Only a few studies have revealed the role of circRNAs in ferroptosis and GBM.…”
Section: Discussionmentioning
confidence: 99%
“…CircLMO1 suppresses cervical cancer growth and promotes cervical cancer cell ferroptosis through up-regulating ACSL4 expression [ 18 ]. However, as master regulators of various cellular processes [ 19 ], it is worth studying novel circRNAs regulate ferroptosis in GSCs.…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs are considered to be major regulators of various cellular processes, and their dysregulation is implicated in all features of cancer (Balihodzic et al, 2021). More and more evidence confirmed the importance of lncRNA in regulating ferroptosis (Balihodzic et al, 2022). LncRNAs can regulate the expression of GPX4 and induce lipid peroxidation of the cell membrane through sponge miRNAs, resulting in the ferroptosis of cancer cells (Zuo et al, 2022).…”
Section: Implications Of Ferroptosis-related Genes For the Genetics O...mentioning
confidence: 99%
“…NcRNAs can regulate cancer progression outside the primary cancer cells via EV-mediated transfer to recipient cells [ 9 ]. EV-ncRNAs are master regulators of various cellular processes and play an important role during carcinogenesis [ 10 ]. Tumor cell-derived EV-ncRNAs influence epithelial-mesenchymal transition (EMT), cell proliferation, metastasis, angiogenesis, drug resistance, and inflammation [ 11 ].…”
Section: Introductionmentioning
confidence: 99%